2016
DOI: 10.1021/acs.chemrestox.6b00055
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pre- and Pro-haptens Using Nonanimal Test Methods for Skin Sensitization

Abstract: Because of ethical and regulatory reasons, several nonanimal test methods to assess the skin sensitization potential of chemicals have been developed and validated. In contrast to in vivo methods, they lack or provide limited metabolic capacity. For this reason, identification of pro-haptens but also pre-haptens, which require molecular transformations to gain peptide reactivity, is a challenge for these methods. In this study, 27 pre- and pro-haptens were tested using nonanimal test methods. Of these, 18 prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 41 publications
4
37
1
Order By: Relevance
“…Similar chemical effects (oxidation of weakly reactive chemicals) can be induced by cytochrome P450, although the activity of these enzymes in human skin is not very high . Of the fragrance compounds studied here, citral, d ‐limonene and linalool were found to be prehaptens, eugenol and isoeugenol are prohaptens, and cinnamyl alcohol and geraniol are both prehaptens and prohaptens . In agreement with these observations, recent experiments showed that benzyl benzoate, benzyl salicylate and benzyl cinnamate remained chemically stable when exposed to forced degradation by oxidation, and remained non‐reactive to cysteine .…”
Section: Discussionsupporting
confidence: 87%
“…Similar chemical effects (oxidation of weakly reactive chemicals) can be induced by cytochrome P450, although the activity of these enzymes in human skin is not very high . Of the fragrance compounds studied here, citral, d ‐limonene and linalool were found to be prehaptens, eugenol and isoeugenol are prohaptens, and cinnamyl alcohol and geraniol are both prehaptens and prohaptens . In agreement with these observations, recent experiments showed that benzyl benzoate, benzyl salicylate and benzyl cinnamate remained chemically stable when exposed to forced degradation by oxidation, and remained non‐reactive to cysteine .…”
Section: Discussionsupporting
confidence: 87%
“…Chemicals identified as Michael acceptors or S N 2 electrophiles have an excellent probability of having their sensitization potential predicted correctly. This fits with what is currently known about the ability of the non-animal assays leading into the network; mainly that the DPRACys and KeratinoSensℱ assays tend to work best with soft electrophiles [38]. While LLNA class prediction was poor for those with an S N 2 domain, it was excellent for Michael acceptors at 76 86 66 %, i.e.…”
Section: Local Validity Analysissupporting
confidence: 82%
“…using the available methods show limitations in the demonstration of concentration-dependency and have limited capacities to detect certain prohaptens and for potency prediction (Piroird et al, 2015;Natsch et al, 2015;Nukada et al, 2012;Teunis et al, 2014;Jaworska et al, 2015;Urbisch et al, 2016;Adler et al, 2011).…”
Section: Discussionmentioning
confidence: 99%